A STUDY ON THE EFFECTIVENESS OF TRANSVAGINAL SONOGRAPHY AND COLOR DOPPLER IN THE ASSESSMENT OF ENDOMETRIUM IN SUBFERTILE WOMEN COMING TO A TERTIARY CARE HOSPITAL. - Bose, Arjita; Kumari, Manisha; Suman, Sanjay; Singh, Kalpana; Jha, Nivedita; Kumar, Kislay (Student's Journal of Health Research Africa, 2024)
Background Ultrasonography (USG) is a very important imaging modality for the diagnosis, treatment, and monitoring of subfertility. Grayscale USG provides structural information about the pelvic organs and color Doppler USG provides functional information along with its vascularity. Adequate blood flow via the uterine arteries and good endometrial perfusion plays a very important role in endometrial receptivity. Objectives The aim and objective of this study is to assess the mid-luteal phase endometrial spiral artery blood flow by TVS including Doppler, in women coming for the treatment of subfertility to a tertiary care hospital. Results Out of 50 patients, primary subfertility comprised 36 individuals while 14 were categorized under secondary subfertility. Most of the patients belonged to the age group of 20-30 years. Of the total number of females 56% conceived, among them 46.43% of patients conceived naturally, followed by IUI (32.14%) and then IVF (21.43%). In our study, 58% of patients presented with an endometrial thickness of over 7 mm, out of which 93.1% conceived successfully. The mean peak systolic velocity in conceived women was 13.18 ± 3.62 cm/s which was higher as compared to 11.55 ± 3.47 cm/s in non-conception menstrual cycles. Similarly, the EDV, Tmax, and Tmin were significantly higher as compared to the not-conceived group. 96.3% of the women who conceived had a lower pulsatility index (< 2.5). The best cut-off value of the resistive index was less than 0.9 for predicting conception status. Conclusion The combination of endometrial thickness and Doppler examination of endometrial and sub-endometrial blood flow can be used as a quick and efficient way to enhance the success of assisted reproductive techniques. Recommendation Due to rapid advancement in Doppler technology, it is highly recommended to perform transvaginal USG including Doppler for assessment of Doppler indices mid-luteal phase in subfertile women coming for treatment.